MODEL PERMAINAN KASVOL DALAM PEMBELAJARAN PENJASORKES KELAS V SEKOLAH DASAR (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The students at the elementary school Rengaspendawa 01 of perceived barriers to participating in learning physical education in particular on the subject of learning under the volleyball serve. Students tend to be passive in teaching physical education. This resulted in limited movement of the child. This study is a research method that refers to the development of models of Borg & Gall development that has been modified The data was collected using field observations and questionnaires were obtained from the evaluation of experts , a small test group and field trials . The data analysis technique used is descriptive percentages. From the test results obtained by the expert evaluation data, a physical education 81.7% (good), learning experts I 85.7% (good), a learning II 86.7% (good). Data is being a small-scale trial results psychomotor aspects of 77.8% (good), cognitive 80% (good), affective 77.8% (good) and large-scale trials psychomotor aspects 85% (good), 95% cognitive ( very good), affective 92.3% (very good). From these results it can be concluded under the model of service learning through play volleyball kasvol fit for use.